Audit Market Response to PCAOB Censures of US Big 4 Firms. Issue 4 (8th August 2019) - Boone, Jeff P.; Khurana, Inder K.; Raman, K. K.
Abstract: Subsequent to the first-ever Public Company Accounting Oversight Board (PCAOB) censure of a US Big 4 firm (Deloitte) in December 2007, there were two other PCAOB US Big 4 firm censures as of 2016 year-end. We examine whether these two post-2007 PCAOB censures of US Big 4 firms conveyed new information to the audit market. For both censures, we find little or no evidence of any change in the factual audit quality of the censured firm over a three-year window surrounding the censure. Our findings suggest that the quality control deficiencies (identified during inspection of specific audit engagements) that triggered the PCAOB censure were isolated occurrences rather than systemic to the firm at large, i.e., the censures do not imply an impairment in the US Big 4 firm's overall factual audit quality. We also find that the negative response of investors and audit committees documented in prior research for the 2007 Deloitte censure disappeared for the later US Big 4 firm censures. Given that the PCAOB inspects (and can censure) non-US auditors who audit US-listed foreign companies, our findings are of potential interest to regulators, investors and audit committees outside the US.